Improving the Nutrient Quality of Juice Waste Mixture by Steam Pressure for Poultry Diet - Mahata, Maria Endo; Rizal, Yose; Wu, Guoyao (Pakistan Journal of Nutrition, 2012)
The problem of juice waste mixture as poultry diet was high in crude fiber and low in metabolizable energy contents. Experiments were performed to improve the nutrient quality of juice waste mixture by using steam pressure. The first experiment was designed in a completely randomized design with 4 different incubation times of juice waste mixture (0, 15, 30, and 45 minutes) in Autoclave (15 psi pressure and 121°C), and each treatment was replicated 5 times. Measured variables were crude fiber, crude protein, crude fat. The second experiment was to compare of crude fiber, crude protein, ether extract, NDF, ADF, cellulose, hemi-cellulose, lignin, nitrogen retention, amino acid profile, and metabolizable energy of juice waste mixture between treated vs. untreated one. The results showed that the crude fiber, crude protein, and crude fat of juice waste mixture were significantly affected (P<0.05) by incubation time in autoclave. The incubation time for 30 minutes decreased crude fiber and crude fat, but increased crude protein contents of the juice waste mixture. The crude fiber, ether extract, NDF, ADF, cellulose, and lignin contents between untreated vs treated reduced from 17.10, 6.24, 34.30, 24.40, 12.20, and 11.80% to 12.02, 4.06, 32.62, 22.05,10.50,11.55%, respectively. Meanwhile, nitrogen retention, crude protein, hemi-cellulose, and metabolizable energy increased from 59.99, 8.40, 9.90%, and 1744 kcal/kg to 65.51, 13.35, 10.57%, and 2550 kcal/kg, respectively. In conclusion, the incubation time for 30 minutes in autoclave was the best treatment for improving the nutrient quality of juice waste mixture.